2010
DOI: 10.1159/000322124
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome and Pregnancy: Follow-Up of Pregnant Women before and after Delivery

Abstract: Aims: To describe the frequency of restless legs syndrome (RLS) in a French population of randomly selected women during their third trimester of pregnancy and its evolution up to 3 months after delivery and to identify potential factors associated with the improvement of RLS after delivery. Methods: A cross-sectional questionnaire survey. Results: 186 pregnant women living in a French town were included. 32% of women were affected by RLS during the third trimester of their pregnancy. Multiple pregnancies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 56 publications
5
55
1
1
Order By: Relevance
“…This yielded 131 articles in Pub Med. Of these, 16 were peer-reviewed articles specifically dealing with the prevalence of WED/RLS during pregnancy and were written in the English language; these 16 articles, spanning 1945 -2012, were included in this review ( Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%
See 3 more Smart Citations
“…This yielded 131 articles in Pub Med. Of these, 16 were peer-reviewed articles specifically dealing with the prevalence of WED/RLS during pregnancy and were written in the English language; these 16 articles, spanning 1945 -2012, were included in this review ( Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%
“…Six studies had participants who completed self-administered questionnaires [17][18][19][20][25][26][27], another seven conducted face to face interviews [16, 21-24, 26, 29, 31], and three studies did not specify how data was collected [28,30,31].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, several epidemiological studies have confirmed an increased prevalence of RLS during pregnancy, with rates of 10%-30% that peak in the third trimester [5][6][7][8] . Notably, although the symptoms tend to resolve after delivery, the recurrence rate in subsequent pregnancies range from 30% to 60% 7 , and women who experience RLS during pregnancy have a three-to four-fold increased risk of developing idiopathic RLS in later life compared with those who had no symptoms during pregnancy.…”
Section: Introductionmentioning
confidence: 96%